SKIN TEMPERATURE MAY NOT YIELD HUMAN BROWN ADIPOSE TISSUE ACTIVITY IN DIVERSE POPULATIONS - Sarasniemi, Jaana (My University, 2019)
18F-FDG-PET have been used in detecting human brown adipose tissue (BAT) for several years. As this research method is very expensive, time consuming and exposes the subjects to ionizing radiation, alternative research methods are needed. The aim of this study was to compare MR spectroscopy and IR thermoscopy as research methods of the activity of brown adipose tissue's baseline metabolism and to examine whether PET, MRI and MR Spectroscopy could be supplemented with infrared (IR) imaging. The study was undertaken in 24 healthy volunteers of which 19 were women. The mean age (±SD) was 48 ± 5 years and BMI was 27,5 ± 5,7 kg/m2. Both IR thermography and MR spectroscopy were measured at room temperature. As expected, there was no association between IR temperatures and fat fraction in the total study population. The association between IR and MRS fat fraction was significant only in subjects with BMI less than 30.